Avaliação cognitiva em pacientes com doença renal crônica no Serviço de Nefrologia de um Hospital Universitário - Ribeiro, Francieli Goulart (2015)
Introduction: Cognitive deficit, including dementia, is a common problem, although little recognized in patients with chronic end-stage renal disease. In patients undergoing hemodialysis prevalence of cognitive impairment has been estimated between 30% and 60%. The causes of this association are not fully established and factors related to chronic kidney disease (CKD) and its treatment may be involved. Contemporary studies suggest that individuals with end-stage chronic kidney disease (CKD-V) have prevalence two to seven times more likely to cognitive decline and dementia when compared to the general population. Addition to prevalent, the condition is associated with a worse prognosis in these patients, including increased risk of dialysis abandonment, hospitalization and death, also implying in higher treatment costs. Objective: Evaluate the prevalence of cognitive decline and dementia in patients on hemodialysis service of the Hospital Universitário Presidente Dutra/ Universidade Federal do Maranhão. Methods: Cross-sectional study in the period August-September 2014, in 69 patients with dialysis CKD, aged 18 years, duration of dialysis more than one month, stable clinical condition without hospitalization for acute events in the last 30 days, eyesight and hearing sufficient to complete the cognitive tests. Cognitive function was assessed by applying two cognitive tests, the Mini-Mental State Examination and the Clock Drawing Test, and daily quality of life scale for analysis of the impact on daily activities of the participants. The adequacy of dialysis was evaluated by the Kt/V single pool (SPKT/V) and the percentage of removal of urea (PRU). Results: Among the 69 participants in the study, mean (SD) age was 43.5 years (17.2); 55% were women, 43% were black and 76% were hypertensive. 51% of respondents have more than 8 years of schooling and 16% are illiterate. The MMSE was amended on 8 participants (11.5%). The clock test was altered in 38 participants (55%), of these 19.4% of male participants and 50% of women (p = 0.030). Among patients with MMSE altered all had impairment in activities of daily living (QAVD) (p = 0.019). Participants with abnormal watch had prejudice of QAVD (p = 0.001). The mean (±) of the Kt / V was 1.59 (0.41), and the PRV was 72.09% (6.93). There was no statistically significant relationship between cognitive decline and values of SPKT / V or PRU. Conclusion: Hemodialysis patients have cognitive impairment with greater impairment of executive functions. The isolated use of MMSE in dialysis patients would not be indicated as these patients may have cognitive impairment, even with normal MMSE. Lower levels of SPKT / V or PRU are not associated with worse cognitive performance. Future studies should confirm these results in longitudinal analyzes.